Seasonal patterns in the epidemiology of Bell's palsy in Hungary - Varga, Eszter; Battamir, Ulambayar; Szegedi, István; Hudák, Lilla; Kovács, Nóra; Nagy, Attila Csaba (Frontiers in Neurology, 2023)
Introduction Epidemiological data on Bell's palsy are vital for elucidating disease prevalence and enhancing therapeutic options. Our objective was to explore the prevalence and possible risk factors associated with Bell's palsy recurrence in the Clinical Center of the University of Debrecen service area. Secondary data analysis was performed using hospital discharge data, including patient information and comorbidities. Methods Data was obtained from the Clinical Center of the University of Debrecen, on Bell's palsy patients who were treated at the hospital between January 1, 2015 and December 31, 2021. Multiple logistic regression analysis was used to examine the factors associated with Bell's palsy recurrence. Results Of the 613 patients analyzed, 5.87% had recurrent paralysis, and the median time interval between episodes was 315 days. Hypertension was significantly associated with Bell's palsy recurrence. Moreover, seasonal distribution analysis revealed that the number of Bell's palsy episodes was higher in colder seasons, with spring and winter having a significantly higher number of episodes than summer and autumn. Discussion This study provides insights into the prevalence and associated risk factors of Bell's palsy recurrence, which could aid in its management and help reduce the long-term consequences of the disease. Further research is necessary to determine the precise mechanisms underlying these findings.